Floating or settling down: the effect of rural landholdings on the settlement intention of rural migrants in urban China. (September 2015) - Hao, Pu; Tang, Shuangshuang
The industrialization and urban development in China have driven a huge portion of the rural population to its urban areas. While discriminating institutions engendered by the hukou system exclude most rural migrants from urban rights and benefits, the option of converting hukou has become increasingly available. Nevertheless, few rural migrants have chosen to settle down in cities by obtaining an urban hukou, which contradicts a common perception that rural migrants desire an urban hukou . Based on a recent migrant survey in Jiangsu Province, this paper explores rural migrants' intention of hukou conversion with respect to the availability, type, and quantity of rural landholdings in their home countryside, as well as their socioeconomic attributes and migration patterns. The results of regression analyses indicate that both the possession of farmland and housing land in rural areas significantly influences the intention of rural migrants to obtain an urban hukou in their destination cities. Moreover, systematic variances in settlement intention are found between the "born-after-1980" generation and their older counterparts, as well as between migrants from the more and less affluent regions. These findings suggest that the decision of hukou conversion incorporates varied concerns and purposes among rural migrants in Chinese cities, which should be addressed with more responsive rural and urban policies.